2007
DOI: 10.4049/jimmunol.178.10.6320
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Repertoire Development in Fetal and Neonatal Piglets: XIX. Undiversified B Cells with Hydrophobic HCDR3s Preferentially Proliferate in the Porcine Reproductive and Respiratory Syndrome

Abstract: Porcine respiratory and reproductive syndrome virus (PRRSV) causes an extraordinary increase in the proportion of B cells resulting in lymphoid hyperplasia, hypergammaglobulinemia, and autoimmunity in neonatal piglets. Spectratypic analysis of B cells from neonatal isolator piglets show a non-Gaussian pattern with preferential expansion of clones bearing certain H chain third complementary region (HCDR3) lengths. However, only in PRRSV-infected isolator piglets was nearly the identical spectratype observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 90 publications
2
44
0
1
Order By: Relevance
“…More recently, we have shown that this syndrome is also associated with the apparent dissemination of certain B cell clones throughout the body (see Fig. 2) that preferentially bear BCRs with hydrophobic H chain CDR3 (HCDR3) regions (6). Skewing of hydropathicity profiles toward B cells with hydrophobic binding sites is unusual in mice and humans (7)(8)(9) and was not observed in littermates infected with SIV, sham controls, young pigs infected with helminthic parasites, or in newborn piglets (6).…”
Section: P Orcine Reproductive and Respiratory Syndrome (Prrs)mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we have shown that this syndrome is also associated with the apparent dissemination of certain B cell clones throughout the body (see Fig. 2) that preferentially bear BCRs with hydrophobic H chain CDR3 (HCDR3) regions (6). Skewing of hydropathicity profiles toward B cells with hydrophobic binding sites is unusual in mice and humans (7)(8)(9) and was not observed in littermates infected with SIV, sham controls, young pigs infected with helminthic parasites, or in newborn piglets (6).…”
Section: P Orcine Reproductive and Respiratory Syndrome (Prrs)mentioning
confidence: 99%
“…2) that preferentially bear BCRs with hydrophobic H chain CDR3 (HCDR3) regions (6). Skewing of hydropathicity profiles toward B cells with hydrophobic binding sites is unusual in mice and humans (7)(8)(9) and was not observed in littermates infected with SIV, sham controls, young pigs infected with helminthic parasites, or in newborn piglets (6). However, that study did not randomly sample B cell clones, so the size of the subpopulation could not estimated and the source of the expanded clones with regard to either V H gene usage or isotype expression was not identified.…”
Section: P Orcine Reproductive and Respiratory Syndrome (Prrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Separation of CDR3 regions for Ig HCs on polyacrylamide sequencing gels provides a clonotypic analysis of BCR repertoire (22,23). This procedure is called CDR3 length analysis or spectratyping and was performed on unsorted or sorted B-lineage populations to show their level of selection for IF rearrangements (18).…”
Section: Cdr3 Spectratypingmentioning
confidence: 99%
“…This procedure is called CDR3 length analysis or spectratyping and was performed on unsorted or sorted B-lineage populations to show their level of selection for IF rearrangements (18). Technically, the CDR3 segments of the amplified VDJs from DNA were reamplified in the third round of PCR using an FR3 up primer that anneals to all porcine V H genes and a [ 32 P]-labeled J H down primer (22,23). The products were separated on sequencing gels that were dried and images were obtained by fluorescent image analyzer FLA-7000 (Fujifilm, Tokyo, Japan).…”
Section: Cdr3 Spectratypingmentioning
confidence: 99%